KETERHUBUNGAN DAN BATASAN ANTARA PERPUSTAKAAN, MASYARAKAT INFORMASI DAN DEMOKRASI: SEBUAH STUDI RINTISAN - Purwanto Putra; Renti Oktaria (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
This research was aimed to examine and tries to see the interrelationships and boundaries between the three components of library, information society and democracy in a pilot study. The study of the relationship of democracy as well as its boundaries with the information society and libraries will try to fill in the blanks regarding information that can be filled in to "patch all leaks" and "imperfection for imperfection". This study uses a qualitative method with the aim of knowing the role of library in information society and democracy . Data collection techniques in this study is to conduct literature reviews and experimental concept. The result of this research showed antara perpustakaan, information society has a strong connection to democracy. Democracy is a very broad term and libraries and society are one of its components.